FEATURES OF ADAPTATION OF SENSORY SYSTEMS OF ATHLETES IN SWIMMING WITH FINS - Dyakova, E.Yu.; Mironov, A.A. (Theory and Practice of Physical Culture, 2022)
Objective of the study was to identify the features of the adaptation of the sensory systems of the body of athletes involved in swimming with fins. Methods and structure of the study. The indicators of three groups were compared: those who go in for finswimming (diver swimmers), those who go in for classical swimming, and those who go in for general physical training (GPT). The age of the examined is 18-23 years. The study was conducted on a day off from training using the "Simple visual-motor reaction" technique. To carry out the statistical method, the Mann-Whitney U test was used. Results and conclusions. As a result of the experiment, it was revealed that in the group of swimmers-submariners, the reaction rate is higher, and there is also less dispersion of results compared to the group of general physical education. Similar results were also observed when comparing the performance of the classical swimming group and the GPT group. There were no significant differences in the obtained results between the sportsmen-submariners and swimmers of classical swimming. Based on the results obtained, it can be concluded that under the influence of many years of training, the speed of sensorimotor reactions increases both in swimmers engaged in fins and in classical swimming.